Impact of lifestyle and physical activity on bone mineral density in adults - Hassan Mubeen; Danish Latif; M Faheem Afzal; Adeela Arif; Haseeb Raza Khan; M Ali Rehman (Journal Riphah College of Rehabilitation Sciences, 2021)
OBJECTIVE: To determine the Effects of physical activity on bone mineral density in young adults.